TLS in Tumors: What Lies Within. Issue 1 (January 2016) - Sautès-Fridman, Catherine; Fridman, Wolf Herman
Abstract : The role of tertiary lymphoid structures (TLS) in cancer has recently been illustrated and revisited using mouse models. Joshi et al. describe regulatory T (Treg) cell infiltration and functional heterogeneity of TLS in lung tumors. Finkin et al. report that inflammation-associated TLS serve as niche for tumor progenitor cells, which may lead to recurrence in hepatocellular-carcinoma.